Flexor tendon xanthomas revealed by digital flexion contracture: Radiological findings - Basma Dghoughi, MD; Hajar Andour, MD; Basma Beqqali, MD; Nazik Allali, PhD; Siham El Haddad, PhD; Latifa Chat, PhD (Radiology Case Reports)
Familial hypercholesterolemia is a hereditary condition marked by persistent high levels of low-density lipoprotein cholesterol in the bloodstream. Alongside the severe premature cardiovascular risks it poses, this condition can manifest in early childhood with cholesterol deposits especially within tendons, known as xanthomas, causing discomfort and thickening of tendons, and rarely movement limitation. Visual examination, manual palpation, and the use of ultrasound to assess tendon thickness and texture are used to suspect the diagnosis. MRI along with biological findings and familial context confirms the diagnosis pf xanthomas. Misidentifying xanthomas can lead to delays in initiating vital lipid-lowering treatments that could potentially save lives. We report the case of a 6 years old child with familial hypercholesterolemia, presented to our structure to investigate a digital flexion contracture, that revealed profound flexor tendons’ xanthomas.